DAS WORT GOTTES UND SEIN GEWAND. EINIGE ÜBERLEGUNGEN ZU OFFB 19,13 - Witetschek, Stephan Joseph (Sacra scripta, 2009)
In Rev 19,13 Christ, returning for the eschatological battle and final judgment, is depicted with a robe “soaked in blood”. The interpretation of this image is often closely related to the OT reference text Isa 63,3, where YHWH appears as the Divine Warrior, so that in Rev 19,13 the blood is that of Christ’s enemies. However, this interpretation faces some exegetical difficulties that can be avoided if one understands that blood as Christ’s own. Moreover, this “nonviolent” interpretation coheres better with the particular significance John attributes to the clothing of the characters in Revelation, and with the Christology of this book, that consciously tackles the tension between Christ’s humiliation and suffering and his resurrection and divine dignity.